On the potential of a chemical Bonds: Possible effects of steroids on home run production in baseball. - Tobin, Roger G. (Tufts University. Tisch Library., 2017)
In recent years several baseball players have hit a remarkable number of home runs, and there has been speculation that their achievements were enhanced by the use of anabolic steroids. Basic mechanics and physiology, combined with simple but reasonable models, show that steroid use by a player who is already highly skilled could produce such dramatic increases in home run production. Because home runs are relatively rare events on the tail of a batter's range distribution, even modest changes in bat speed can increase the proportion of batted balls that result in home runs by 50-100%. The possible effect of steroid use by pitchers is briefly considered.